1994
DOI: 10.1080/01904169409364706
|View full text |Cite
|
Sign up to set email alerts
|

Efect of zinc and iron deficiency on phytos1derophore release in wheat genotypes differing in zinc efficiency

Abstract: The effect of varied zinc (Zn) and iron (Fe) supply on the release of Zn and Fe mobilizing phytosiderophores from roots was studied in Zn-efficient Aroona and Zn-inefficient Durati wheat genotypes (Triticum aestivum cv. Aroona; T. durum cv. Durati) grown under controlled environmental conditions in nutrient solution for 25 days. Phytosiderophore release was determined by the measurement of Zn and Fe mobilizing capacity of root exudates from a Zn-loaded resin and from freshly precipitated Fe III hydroxide as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Measured exudation rates are in a comparable range with release rates of Fe deficient wheat (Cakmak Triticum aestivum cv Aroona, 25 days old, 1.14 nmol g −1 s −1 ) and other grasses reported in the literature (e.g. Clark Hordeum vulgare cv Europa, 19 days old, 3.1 nmol g −1 s −1 ) with values from literature here being converted to SI units for better comparability.…”
Section: Resultssupporting
confidence: 63%
“…Measured exudation rates are in a comparable range with release rates of Fe deficient wheat (Cakmak Triticum aestivum cv Aroona, 25 days old, 1.14 nmol g −1 s −1 ) and other grasses reported in the literature (e.g. Clark Hordeum vulgare cv Europa, 19 days old, 3.1 nmol g −1 s −1 ) with values from literature here being converted to SI units for better comparability.…”
Section: Resultssupporting
confidence: 63%
“…Zinc deficiency increases the secretion of MAs from wheat and barley roots into the rhizosphere (Cakmak et al . 1994; Walter et al .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Zn deficiency increases the secretion of MAs from wheat and barley roots into the rhizosphere (Cakmak et al, 1994;Walter et al, 1994;Zhang et al, 1989). However, other studies have shown that significant secretion of MAs from barley or wheat only occurs in plants deficient in Fe, and not in those suffering Zn deficiency (Gries et al, 1995;Pedler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%